PARADIGMA EKO-EFISIENSI DALAM AKUNTANSI BIAYA SEBAGAI PEMBENTUK PREFERENSI PENGAMBILAN KEPUTUSAN MANAJER PERHOTELAN BAGI PEMBANGUNAN BERKELANJUTAN - , Wika Harisa Putri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Ecoefficiency has became important discourse in business worldsince emerged in the World Business Council on Sustainable Development (WBCSD) forum in 1992. It is considered to be one of starting point for sustainable development. However, efforts to implement ecoefficiency faces many challenges, especially related to cost effectiveness and investment value. Though it is predicted to be succeed in saving resources, many professional managers still doubt to implement it. It made command and controal approach oftenly used to implement the ecoefficiency concept. The study proves that the policy influence, as manifestation of command and control approach, still dominating the eco-efficiency implementation in the business world. Using conjoint analysis method and hotel managers as respondents, the study proves that the ecoâ-efficiency will become managersâ preference when the benefits of the economic aspect seem to be more predominant than the benefit of environment aspect.